Assessment of glycosaminoglycan content in intervertebral discs of patients with leg length discrepancy: A pilot study. - Latz, David; Frenken, Miriam; Schiffner, Erik; Knautz, Maxime; Quante, Wolfgang Alois; Windolf, Joachim; Grassmann, Jan Peter; Jungbluth, Pascal; Schleich, Christoph (Journal of Orthopaedics)
Objective: Leg length discrepancy (LLD) could be a predisposing factor for early degeneration of lumbar intervertebral discs (IVD). The purpose of this study was to elucidate the molecular effect of LLD on IVDs. Methods: IVDs of Eleven patients (25.6 ± 4.3years) with LLD (> 10 mm) and 14 control subjects (23.9 ± 3.5years) were compared using a 3T-MR scanner. Morphological T2-weighted and glycosaminoglycan-chemical- exchange-saturation-transfer (gagCEST) sequences were performed. Results: No differences in morphological Pfirrmann grading were found (p > 0.05). In contrast, nucleus-pulposus-gagCEST-values of L5/S1 were significantly lower (p=0.0008). Conclusion: Our results suggest that LLD is a predisposing factor for molecular IVD alterations, which are detectable even before morphological pathologies could be found.